When unexpected guests come to eat: two new species of Phyllolabis Osten Sacken (Diptera: Limoniidae) collected with carrion-baited traps in the centre of the Iberian Peninsula - Mederos, Jorge; Martín-Vega, Daniel; Baz, Arturo (Zootaxa, 2021)
Phyllolabis eiroae sp. nov. and P. martinhalli sp. nov. are described from the centre of the Iberian Peninsula. These two remarkable species were collected using carrion-baited traps, running during winter, in several localities of Madrid province (Spain). The two new species are well differentiated from the other Phyllolabis Osten Sacken species recorded from the Iberian Peninsula, P. savtshenkoi Theowald, and those from the west Palaearctic. An identification key to differentiate the three Phyllolabis species occurring in the Iberian Peninsula is provided. The first images of P. savtshenkoi, based on the holotype and a male specimen recorded from a cave located in Jaén (Spain), are also provided.